Navigating New Beginnings: A Study of State-Level Grant Funding Support for K-12 Refugee Education - Emily R. Crawford; Juan José Reyes; Oksana Kozlova; Lisa Dorner (Social Sciences)
In 2022, the federal government initiated two grant programs geared to enhance education specifically for Afghan and Ukrainian populations: the Afghan Refugee School Impact and Support to Schools supplements, both part of the Refugee School Impact (RSI) program. In Missouri, the context of our research, RSI funding has been coordinated by a non-profit organization, the Missouri Office for Refugee Administration (MO-ORA). In partnership with MO-ORA, we designed a qualitative study and used content analysis to examine 39 RSI grant applications to MO-ORA from 35 different districts. We explored two key research questions: (1) what did K-12 schools in Missouri identify as priorities to support refugee students in their RSI grant applications? and (2) how did districts plan to allocate resources to meet refugee students’ and families’ perceived needs? Analyses identified that districts’ biggest priorities were to support: (1) family engagement activities, (2) English Learners’ education, and (3) student English language proficiency. Meanwhile, districts’ top three areas of funding allocation went to the pre-named categories of Student Services for Els, Professional Development for Staff, and Facilitating Partnerships.